2019
DOI: 10.28918/ijibec.v3i1.1567
|View full text |Cite
|
Sign up to set email alerts
|

The The Effect of Expert Management, Professional Skepticism And Professional Ethics On Auditors Detecting Ability With Emotional Intelligence As Modeling Variables

Abstract: This study aims to examine the effect of management experts, professional skepticism and professional ethics on the auditor's ability to detect fraud with intelligence emotional as a moderating variable. This research was conducted at the Makassar City Inspectorate. This research is an explanatory study with a quantitative approach. The study used a saturated sample method with a sample of 25 people. Analysis data in this research using multiple regression analysis with absolute difference value. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
(10 reference statements)
1
6
0
1
Order By: Relevance
“…In a study on emotional intelligence in which self-awareness is the first component, Wang and Zhang (2020) showed that emotional intelligence did not impact the relationship between social support and unhealthy internet use behavior. Also, Awaluddin et al (2019) and Zaini and Musyarofah (2020) could not prove the moderating effect of emotional intelligence on the relationship between knowledge, experience, and professional ethics on the ability to detect financial fraud. Although the study was not related to adoption behavior, it was relevant enough to confirm the results of this study.…”
Section: Figure 2 Structural Model and Parameter Estimation Resultsmentioning
confidence: 94%
“…In a study on emotional intelligence in which self-awareness is the first component, Wang and Zhang (2020) showed that emotional intelligence did not impact the relationship between social support and unhealthy internet use behavior. Also, Awaluddin et al (2019) and Zaini and Musyarofah (2020) could not prove the moderating effect of emotional intelligence on the relationship between knowledge, experience, and professional ethics on the ability to detect financial fraud. Although the study was not related to adoption behavior, it was relevant enough to confirm the results of this study.…”
Section: Figure 2 Structural Model and Parameter Estimation Resultsmentioning
confidence: 94%
“…This includes skills such as emotional understanding, emotional regulation, selfmotivation, and the ability to form healthy relationships with others [9]. Internal auditors are professionals responsible for evaluating and monitoring organizational compliance and performance, and providing recommendations for improvement [7]. Audit judgment refers to the internal auditor's ability to make appropriate decisions and assessments in carrying out their audit tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Auditors with higher levels of emotional intelligence tend to be more effective in detecting fraud and ethical violations within the company [7]. Auditors with higher levels of emotional intelligence tend to have better abilities in managing stress, improving audit performance, and reducing errors in auditing [8].…”
Section: Introductionmentioning
confidence: 99%
“…Skeptime profesional yang ada dalam diri auditor BPKP menimbulkan prilaku yang percaya diri untuk meningkatkan kemampuan mendeteksi kecurangan. Hasil penelitian ini jugamendukung penelitian Soenanto & Pesudo (2020); Awaluddin et al (2019); Purba & Nuryatno (2019) menyatakan bahwa skeptisme professional berpengaruh positif terhadap kemampuan auditor mendeteksi kecurangan.…”
Section: Skeptisme Profesional Terhadap Kemampuan Auditor Mendeteksi ...unclassified